Moderated mediation approach to determine the effect of natural packaging factors on intention to purchase natural skincare products among the population of Klang Valley, Malaysia. Issue 2 (18th January 2023) - Najm, Ahmed Abdulkareem; Salih, Sarah Abdulkareem; Fazry, Shazrul; Law, Douglas; Azfaralariff, Ahmad
Abstract: The trends for health and pro‐environmental behaviors led to motivating consumers' attention to use natural skincare products. Purchase intention for natural skincare products can be influenced by several environmental, behavioral, and external factors. In line with global trends, the current study aims to determine the moderated mediation path in the relationship between the aspects of natural packaging of natural skincare products (environmental concerns, packaging design, and printed information), and the intention to purchase natural skincare products purchase intention. A web‐based survey was used to gather quantitative data from a convenience sample of 330 participants from Klang Valley, Malaysia. The study outcomes revealed that personal attitude significantly mediated the effect of environmental concerns, natural packaging design, and package printed information on purchase intention. Most importantly, the product safety certificate had a significant moderated mediation effect on the model of environmental concerns, natural packaging design, and purchase intention for natural skincare products. The results contributed to the information and recommendations for stakeholders to consider the packaging factors and safety certificates in the purchase behavior models in promoting the natural skincare products' marketing and industry. Practical Application: The significance of the study lies in the linkage of graphic design to sustainability and marketing management research.